The Effect of Matoa (Pometia pinnata) Leaves Ethanol Extract On Reducing Cholestrol Levels In Male Mice (Mus musculus) - Haq, Muhammad Naufal Syaiful; Pagarra, Halifah; Muis, Abd.; Salsabila, Shopia (Sainsmat : Jurnal Ilmiah Ilmu Pengetahuan Alam, 2025)
This research aims to determine the total phenolic content and antioxidant activity of the ethanol extract of matoa (Pometia pinnata) leaves and their effect on the cholesterol levels of male mice (Mus musculus). To determine the total phenolic content using the Folin-Ciocalteu method and the DPPH method to measure antioxidant activity. The effect of matoa leaf extract on reducing cholesterol levels in mice used a completely randomized design (CRD) with 15 mice divided into 5 treatment groups with 3 replications, namely P1 (Extract 175 mg/kgBW), P2 (Extract 350 mg/kgBW), P3 (Extract 700 mg/kgBW), K+ (Simvastatin 0.10 mg/kgBW), and K- (Na-CMC 1%). Extraction uses the maceration method with 70% ethanol solvent. The total phenolic test results were 26.24872 mgGAE/g. The results of measuring antioxidant activity obtained an IC50 of 1,961 ppm. The results of testing cholesterol levels showed that there was an effect of giving ethanol extract of Matoa (Pometia pinnata) leaves on reducing cholesterol levels in male mice (Mus musculus). Giving ethanol extract of Matoa leaves at a dose of 350 mg/kgBW is effective in reducing cholesterol levels. So it can be concluded that the ethanol extract of Matoa leaves has an effect on reducing cholesterol levels in male mice.